2020
DOI: 10.3390/ijms21249704
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside M1 Induces Apoptosis and Inhibits the Migration of Human Oral Cancer Cells

Abstract: Oral squamous cell carcinoma (OSCC) accounts for 5.8% of all malignancies in Taiwan, and the incidence of OSCC is on the rise. OSCC is also a common malignancy worldwide, and the five-year survival rate remains poor. Therefore, new and effective treatments are needed to control OSCC. In the present study, we prepared ginsenoside M1 (20-O-beta-d-glucopyranosyl-20(S)-protopanaxadiol), a major deglycosylated metabolite of ginsenoside, through the biotransformation of Panax notoginseng leaves by the fungus SP-LSL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Protopanaxadiol (PPD) is one of two metabolites of ginsenoside, the main components extracted from ginseng. There are many reports about PPD used to treat various tumors, cardiovascular diseases 28 , 29 . Additionally, our previous study has showed that PPD suppresses ER-mediated inhibition of endometriotic cells autophagy, contributing to anti-EMs effects 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Protopanaxadiol (PPD) is one of two metabolites of ginsenoside, the main components extracted from ginseng. There are many reports about PPD used to treat various tumors, cardiovascular diseases 28 , 29 . Additionally, our previous study has showed that PPD suppresses ER-mediated inhibition of endometriotic cells autophagy, contributing to anti-EMs effects 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers investigated that ginsenoside M1 caused an increase in Bak, Bad, and p53 expression and induced apoptotic DNA fragmentation. 41 It also caused PI/Annexin V double positive staining and caspase 3-9 activation, which led to apoptosis of oral cancer cell. Additionally, ginsenoside M1 inhibited cancer cell migration and colony formation, whilst decreasing the expression of vimentin and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [98] found that 20(S)-ginsenoside Rh2 (63) induces the apoptosis and inhibits the growth of OCC by inducing G0/G phase arrest and significantly down-regulating the levels of p-Src, p-B-Raf, and p-ERK1/2 proteins. Li et al [99] found that ginsenoside M1 induces cell apoptosis by increasing the expression of pro-apoptotic protein p53, promoting DNA breakage, and inhibiting the cell cycle. In addition, ginsenoside M1 (64) dose-dependently inhibits the colony formation and migration of SAS and OEC-M1 cells and reduces the expression of the transfer-related protein vimentin.…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%